2006
DOI: 10.1103/physrevlett.96.112501
|View full text |Cite
|
Sign up to set email alerts
|

Efimov Effect in Nuclear Three-Body Resonance Decays

Abstract: We investigate the effects of the nearly fulfilled Efimov conditions on the properties of three-body resonances. Using the hyper-spheric adiabatic expansion method we compute energy distributions of fragments in a three-body decay of a nuclear resonance. As a realistic example we investigate the 1 − state in the halo nucleus 11 Li within a three-body 9 Li + n + n model. Characteristic features appear as sharp peaks in the energy distributions. Their origin, as in the Efimov effect, is in the large two-body s-w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
1
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 15 publications
(30 reference statements)
0
44
1
1
Order By: Relevance
“…2 together with the results of the DWBA calculations. Some disagreements may be connected with the influence of the 5 He transfer reaction reflecting the predicted [1,3] contribution of the 5 He + 4 He configuration in the 9 Be structure. The latter one possibly manifests itself in the strong oscillation structure at the backward angles (Fig.3), as observed at E (α) = 50 MeV [9].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 together with the results of the DWBA calculations. Some disagreements may be connected with the influence of the 5 He transfer reaction reflecting the predicted [1,3] contribution of the 5 He + 4 He configuration in the 9 Be structure. The latter one possibly manifests itself in the strong oscillation structure at the backward angles (Fig.3), as observed at E (α) = 50 MeV [9].…”
Section: Resultsmentioning
confidence: 99%
“…The head of the second band is the first excited state 1/2 + , 1.68 MeV (σ-band, K = 1/2 + ) located only 15 keV above the 8 Be + n threshold. This particular level was the object of intensive theoretical study and is considered to be either a virtual state [2] or a combination of 5 He + 4 He and 8 Be + n configurations [3]. Accordingly, both bands are characterized by large moments of inertia, which are either equal to that of 8 Be (the π-band) or even larger (the σ-band).…”
Section: Introductionmentioning
confidence: 99%
“…The cluster configuration of 8 Be + n dominates in the internal structure of 9 Be (see [1] and refs. there), however, the 5 He + 4 He one also can play some role [2]. Possessing very large deformation parameter 9 Be has two well developed rotational bands (π-band, K = 3/2 -) and (σ-band, K = 1/2 + ) based on the ground and the first excited (1.68 MeV) states correspondingly.…”
Section: Introductionmentioning
confidence: 98%
“…Recent studies with trapped ions [40,41] showed that these Efimov states really manifest themselves when being specifically set up in the freely tunable environment of a tailored quantum system. For nuclear systems these conditions have to be met by finding the necessary boundary conditions by selecting a three-body system with the appropriate interactions [42] in the binary subsystems.…”
Section: The Stepping Stone: Properties Of 11 LImentioning
confidence: 99%